2016
DOI: 10.1103/physreva.93.053817
|View full text |Cite
|
Sign up to set email alerts
|

Programmable two-photon quantum interference in103channels in opaque scattering media

Abstract: We investigate two-photon quantum interference in an opaque scattering medium that intrinsically supports 10 6 transmission channels. By adaptive spatial phase-modulation of the incident wavefronts, the photons are directed at targeted speckle spots or output channels. From 10 3 experimentally available coupled channels, we select two channels and enhance their transmission, to realize the equivalent of a fully programmable 2 × 2 beam splitter. By sending pairs of single photons from a parametric down-conversi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 46 publications
0
56
0
Order By: Relevance
“…In QIP, non-unitary, lossy, transformations are typically considered detrimental. However, the additional freedom obtained by removing the restriction of unitarity allows for new transformations that exhibit exciting behavior such as a tunable quantum interference and an apparent nonlinear absorption [55,60,61]. Already the simple case of a balanced symmetric lossy beam splitter contains free parameters determining the relative phase of the transmission coefficients that enable the tuning of the well-known HOM-like dip, the signature of bosonic coalescence, into a HOM-peak for bosonic anti-coalescence.…”
Section: Arbitrary Linear Transformationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In QIP, non-unitary, lossy, transformations are typically considered detrimental. However, the additional freedom obtained by removing the restriction of unitarity allows for new transformations that exhibit exciting behavior such as a tunable quantum interference and an apparent nonlinear absorption [55,60,61]. Already the simple case of a balanced symmetric lossy beam splitter contains free parameters determining the relative phase of the transmission coefficients that enable the tuning of the well-known HOM-like dip, the signature of bosonic coalescence, into a HOM-peak for bosonic anti-coalescence.…”
Section: Arbitrary Linear Transformationsmentioning
confidence: 99%
“…We show that our processor preserves the coherence of quantum states by programming the processor to implement quantum interference. As a proof-of-principle demonstration of the architecture's capability to implement non-unitary transformations, we show anti-coalescence of bosons [54][55][56] on a 2×2 Blass matrix. Finally, we realize high-dimensional single-photon quantum gates exploiting the whole spatial mode structure of the processor.…”
Section: Introductionmentioning
confidence: 96%
“…First, propagation losses will be revisited for plasmonic N00N states. Second, we use a lossy beamsplitter which enables us to modify the phase difference between reflection and transmission coefficients [10][11][12][13][14][15][16]. It has been shown that this effect may induce nonlinear absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Many classical and quantum applications rely on this approach [12], ranging from spatial mode structuring [13][14][15] to adaptive quantum optics and communication [16,17]. As for linear circuits, programmable beamsplitters have been implemented in opaque scattering media [18][19][20] and multimode fibers [21] through control of spatial mode mix- * sylvain.gigan@lkb.ens.fr ing. In this work, we report the implementation of fully programmable linear optical networks of higher dimensions by harnessing spatial and polarization mixing processes in a multimode fiber driven by wavefront shaping.…”
mentioning
confidence: 99%